A portable instrument for rolling resistance characterization of roller ski wheels - Löfgren, A.; Hansson, A.; Larsen, J.; Sandström, A.; Kuylenstierna, D. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: The rolling resistance of a roller ski wheel constitutes an important factor determining the outcome of roller ski competitions, yet there is a lack of equipment for effective characterization of the same. In the past this was less of a problem as most competitions were organized without restrictions on allowed wheel types. Each participant could freely select whichever wheel material they deemed most competitively advantageous, similar as is the case on snow. However, in recent years it has become increasingly common for roller ski competitions to restrict which wheel types are allowed, most commonly by restricting allowed wheels to so-called "standard-roll wheels" (also known as "grade-2 wheels"). Nevertheless, there exists no quantitative definition of standard-roll, and the variation among common available brands is large. The situation necessitates an instrument that can characterize the rolling resistance of roller skis with high precision and with efficiency in the testing procedure. A couple of attempts to develop such instruments have been done in the past, e.g., [1] presents an instrument based on a miniaturized treadmill and [2] presents an instrument based on a strain gauge. However, both these set-ups have drawbacks in terms of limited portability and/or that they require the wheels to be separated from the ski. The purpose of this work is to build a portable instrument for non-destructive characterization of roller ski resistance.